Gravity, Distance, and International Trade - Scott L. Baier; Amanda Kerr; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2017)
We review and interpret the main theoretical developments in the gravity literature from its very early, a-theoretical applications to the latest structural contributions. We also discuss challenges and implement methods to estimate empirical gravity equations. We finish with a presentation and examples of numerical simulations with the structural gravity model. Throughout the analysis we attempt to emphasize the links and importance of transportation costs for the trade literature and we outline avenues where we believe interdisciplinary contributions between the international trade and transportation economics fields will be most valuable.
Keywords: F10; F43; O40; 330; structural gravity; estimation; simulation; transportation costs